2010
DOI: 10.4315/0362-028x-73.9.1688
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Listeria monocytogenes in Retailed Meat in the Tokyo Metropolitan Area

Abstract: This study was conducted to determine the prevalence of Listeria monocytogenes in retailed meats, comprising beef, chicken, and pork, in the Tokyo metropolitan area. A total of 379 samples of retailed meat were collected from 1998 to 2003, most of which were obtained by simultaneously purchasing the three classes of meat from a shop and then making another simultaneous purchase of meat from the same shop a few weeks later. The prevalence of L. monocytogenes was 28.0%, and the serotypes isolated were mainly 1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
5
19
2
Order By: Relevance
“…monocytogenes is a food-transmitted pathogen with implications in the food industry due to its ubiquitous nature. This feature allows the bacterium to be disseminated in the environment, facilitating accession to meat-processing plants, in particular pork-meat processing product plants, favoring food contamination (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…monocytogenes is a food-transmitted pathogen with implications in the food industry due to its ubiquitous nature. This feature allows the bacterium to be disseminated in the environment, facilitating accession to meat-processing plants, in particular pork-meat processing product plants, favoring food contamination (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…(20,28). The conditions of contact surfaces and equipment affect the persistence of L. monocytogenes.…”
Section: Pork Meat Derivatesmentioning
confidence: 99%
“…Bacterial strains: Twenty-eight strains of L. monocytogenes serotype 4b were previously isolated from different classes of retail meat, including beef, chicken and pork, from the Tokyo metropolitan area (Tokyo, Chiba, Kanagawa, Saitama) during the period 1998-2003 (Table 1) (20). In addition, 1 and 3 strains of serotype 4b, which were isolated from retail meat from the same area in 1989 and 1997, respectively, were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…We previously have investigated the prevalence of L. monocytogenes in retail meat collected from the Tokyo metropolitan area over the period 1998-2003 and identified serotype 4b as one of the major serovars frequently isolated from meat samples (20). In addition, our previous study on the genetic variation of this pathogen revealed that certain strains of serotype 4b, which were classified within genotypes on the basis of partial nucleotide sequence of the iap gene, were considered to belong to ECI (21).…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al [22] reported that L. monocytogenes was isolated from the skins of three (5%) of 60 beef cattle sampled at an abattoir, although L. monocytogenes isolates were not obtained from large intestinal contents. Ochiai et al [17] reported that L. monocytogenes was isolated from 15.5% (17/110) of retailed beef samples and that the serovars of the isolates were 1/2a (three isolates), 1/2b (two isolates), 1/2c (eight isolates) and 4b (five isolates). It is possible that beef is contaminated with L. monocytogenes hiding in the skins of cattle at abattoirs.…”
mentioning
confidence: 99%